2012
DOI: 10.1080/17461391.2012.749947
|View full text |Cite
|
Sign up to set email alerts
|

The role of specialisation in the promotion of young football talents: A person‐oriented study

Abstract: This paper investigates the controversial question whether it is more effective to promote specialisation in a specific sport at the beginning of a career, or whether to encourage a broad range of sports when promoting competitive sports talents in order for them to achieve a high level of performance in adulthood. The issue of promoting talents depends on human developmental processes and therefore raises developmental scientific questions. Based on recent, dynamic-interactionist concepts of development, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 30 publications
3
55
0
Order By: Relevance
“…Conzelmann 67 reported players specialising in football at a later age. Such findings indicate that there may be confounding cultural issues within football, that transcend national boundaries, and contribute to a culturally acceptable notion that players should specialise in football above other sports from a young age.…”
Section: And Zibung Andmentioning
confidence: 99%
“…Conzelmann 67 reported players specialising in football at a later age. Such findings indicate that there may be confounding cultural issues within football, that transcend national boundaries, and contribute to a culturally acceptable notion that players should specialise in football above other sports from a young age.…”
Section: And Zibung Andmentioning
confidence: 99%
“…In addition, data available from Portuguese national athletes (including soccer players) showed that the path to expertise were nonuniform, which reflects the complexity of skill acquisition (Leite et al, 2009). Furthermore, in former Swiss professional soccer players, although all players retrospectively reported above average volumes of in-club training, some showed above average participation rates of informal soccer outside the club, whereas, others described greater than average activity in other sports (Zinberg & Conzelmann, 2012). Cumulatively, while not always consistent, the existing literature indicates a more diverse approach to sports participation is preferable.…”
Section: Introductionmentioning
confidence: 99%
“…According to these authors, anthropometric, and physical performance characteristics are considered fundamental for talent identification. The present study expanded on these ideas and tried to determine which anthropometric and physical performance variables, by means of discriminatory analysis, were most significant at the time of selecting male and female handball players; this follows the trend of research established by other academics and practitioners 7,15,16 .…”
Section: Introductionmentioning
confidence: 99%